VICTOR FRANKENSTEIN’S ANXIETY AND DEFENSE MECHANISM AS DEPICTED IN MARY SHELLEY’S FRANKENSTEIN - PUTRI, OKTAVIANI ARNANTA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Psychoanalysis, Freudian Psychology, Anxiety, Defense Mechanism Psychoanalysis is useful to understand human behavior. Psychoanalysis is also useful to help in understanding literary texts, which are about human behavior. This study analyzes Victor Frankenstein, the main character in Mary Shelley’s Frankenstein novel. His psychological condition experiences anxiety and defense mechanism can be analyzed through Freudian’s psychology.Related to this case, this study aims to reveal Victor Frankenstein’s anxiety and how he copes with that by using defense mechanism. This study uses qualitative approach to reveal Victor Frankenstein’s anxiety and defense mechanism as depicted in the novel.This study reveals that Victor Frankenstein experiences anxiety after he creates his creature. He experiences the reality anxiety because of his creature’s appearance. The neurotic anxiety also occurs on him because he often expects something dreadful to happen. And the last, moral anxiety occurs because of his guilty feeling for his family's death. In order to reduce these anxieties, he uses repression, reaction formation and projection as tactics called defense mechanism.